PENGARUH JOB INSECURITY, KEPUASAN KERJA, DAN STRES KERJA TERHADAP TURNOVER INTENTION PADA PT BPR ARTHA PRIMA PERKASA PULAU BATAM - Regina Desvarani; Sastra Tamami (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2019)
The purpose of this study was to determine the effect of Job Insecurity, Job Satisfaction, JobStress on Turnover Intention at PT BPR Artha Prima Perkasa. This study used a quantitative method bydistributing questionnaires to 32 employees who work at PT BPR Artha Prima Perkasa. Samples weretaken by saturated sampling techniques. The data analysis method used is quantitative analysis,namely reliability test and validity test, classic assumption test, T test and F test, coefficient ofdetermination and multiple linear regression analysis.Based on the results of data analysis, it shows that: Job Insecurity variable has a significanteffect on Turnover Intention with T sig value of 0,000 <0,05, job satisfaction variable shows no effect onTurnover Intention with T sig value of 0,624 <0,05 and Job stress has a significant effect on TurnoverIntention with a T sig value of 0,000 <0,05. Based on the F test calculation, together with Job Insecurity,Job Satisfaction, Job Stress has a significant effect on Turnover Intention with F sig 0,000 <0,05.